LINGUISTIC FEATURES OF PREPOSITIONAL PHRASES (Conferencea, 2023)
In world linguistics, problems related to the phenomenon of phraseology have been discussed for a long time. Today in world linguistics researches are being carried out in priority directions such as structural-semantic, communicative-pragmatic, comparative-typological and linguistic-cultural analysis of lexical units related to a certain thematic area within the framework of the study of the unique cognitive mechanisms of linguistic realization and conceptualization of the world in the minds of language owners.